The Relationship between Climate Change and the Prevalence of Environmentally Based Diseases in Coastal Fishing Communities in Abeli District - Indri Reva Wardani; Sarni Tia; Mufida Dwi Agusti; Moon Sari; Astrid Pratiwi Lahata; Nur Ain; Clariza Garda Sakti; Nunung Sari; Muliyati (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Indonesia, as the largest archipelagic country in the world, possesses approximately two-thirds of its territory in the form of marine areas, with a total area of around 3.25 million km². Of this, 2.55 million km² constitutes the Exclusive Economic Zone (EEZ). Indonesia has the right to utilize natural resources both living and non-living within its waters, which span an estimated 7.81 million km². This vast maritime potential offers significant opportunities for the development of the marine and fisheries sector, which serves as a key pillar in national economic growth. Objective: This study aims to examine the relationship between climate change and the prevalence of environmentally-based diseases among coastal fishing communities in Abeli District. Method: This research employed a descriptive-analytical design with a cross-sectional approach. Data collection was conducted through structured interviews involving 200 randomly selected respondents using a standardized research questionnaire. Data were analyzed to explore the correlation between perceived climate change (such as increasing air temperatures) and reported cases of environment-related diseases. Results: The majority of respondents (61.5%) were within the 41–60 year age group. Out of 200 respondents, 32 reported having contracted dengue fever. Among these, 2 respondents (1.0%) perceived an increase in air temperature, while 9 (4.5%) did not. Additionally, 7 respondents reported having malaria, and 5 experienced skin diseases. Of those with skin diseases, 2 (1.0%) perceived a rise in temperature, while 3 (1.5%) did not. These results indicate patterns in the perception of climatic changes associated with the incidence of environmentally-influenced diseases. Conclusion: The findings suggest a significant relationship between climate change and the prevalence of environmentally-based diseases within coastal fishing communities in Abeli District. Therefore, it is imperative to implement effective mitigation strategies through enhanced public health education and the strengthening of health infrastructure to address the challenges posed by climate change. Keywords: Climate Change, Disease Prevalence, Fishing Communities, Coastal, Marine and Fisheries